Study on the mechanism of Danshen-Guizhi drug pair in the treatment of ovarian cancer based on network pharmacology and in vitro experiment - Qin, Chongzhen; Wu, Menglin; Wang, Xinru; Zhang, Wenda; Qi, Guangzhao; Wu, Na-Yi; Liu, Xiaoting; Lu, Yaoyao; Zhang, Jingmin; Chai, Yuna (PeerJ, 2022)
Our study aims to explore the active components and mechanisms of the Danshen-Guizhi drug pair in treating ovarian cancer by network pharmacology and in vitro experiment. The “component-target-pathway” diagram of the Danshen-Guizhi drug pair was established by network pharmacology, and the effective active components, important targets as well as potential mechanisms of the Danshen-Guizhi drug pair were analyzed. The predicted results were verified by molecular docking and in vitro experiments. The main active components of the Danshen-Guizhi drug pair in the treatment of ovarian cancer are salviolone, luteolin, β-sitosterol and tanshinone IIA. The main core target is PTGS2. The pathways involved mainly include the cancer pathway, PI3K-Akt signaling pathway, and IL-17 signaling pathway. The molecular docking results showed that salviolone and tanshinone IIA had good binding ability to the target. The expression of PTGS2 mRNA and PGE2 in ovarian cells were significantly inhibited by salviolone. The mechanism of the Danshen-Guizhi drug pair in the treatment of ovarian cancer may be regulating cell proliferation, apoptosis and tumor immunity. This provides a theoretical basis for the clinical development and application of the Danshen-Guizhi drug pair.
Keywords: Danshen; Guizhi; Core targets; Network pharmacology; Ovarian cancer; Molecular docking